INTER- AND INTRASPECIFIC COMMUNITY STRUCTURE WITHIN THE DIATOM GENUS PSEUDO-NITZSCHIA (BACILLARIOPHYCEAE) - Hubbard, Katherine A. (2008)
Pseudo-nitzschia-specific PCR primers (PnAll F/R) were designed to amplify a polymorphic region of the internal transcribed spacer 1 (ITS1) from at least 11 Pseudo-nitzschia species. The primers were used to generate environmental clone libraries from Puget Sound, Washington, and Vancouver Island, British Columbia, to confirm that the primers were specific for Pseudo-nitzschia and to determine the extent of ITS1 sequence diversity within individual species. All environmental ITS1 sequences generated with PnAll primers displayed the greatest similarity to known Pseudo-nitzschia ITS1 sequences. The length of cloned ITS1 fragments differed among species but was conserved within a species. Intraspecific genotypes exhibited <3% sequence divergence for seven of the 10 species detected in clone libraries. Several ITS1 genotypes unique to the Pacific Northwest were identified in environmental samples, and other genotypes were more broadly distributed. The Pseudo-nitzschia primers were also used to develop an automated ribosomal intergenic spacer analysis (ARISA) to rapidly identify Pseudo-nitzschia species in environmental samples based on species-specific variation in the length of the targeted ITS1 region. The ARISA peaks were then associated with the environmental clone sequences for Pseudo-nitzschia species. Surveying the genetic composition of communities at both the inter- and intraspecific levels will enhance our understanding of Pseudo-nitzschia bloom dynamics.